Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2011
DOI: 10.1016/j.ajpath.2011.04.037
|View full text |Cite
|
Sign up to set email alerts
|

Expression of Endoplasmic Reticulum Stress Proteins Is a Candidate Marker of Brain Metastasis in both ErbB-2+ and ErbB-2− Primary Breast Tumors

Abstract: The increasing incidence of breast cancer brain metastasis in patients with otherwise well-controlled systemic cancer is a key challenge in cancer research. It is necessary to understand the properties of brain-tropic tumor cells to identify patients at risk for brain metastasis. Here we attempt to identify functional phenotypes that might enhance brain metastasis. To obtain an accurate classification of brain metastasis proteins, we mapped organ-specific brain metastasis gene expression signatures onto an exp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
35
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 41 publications
(35 citation statements)
references
References 50 publications
(46 reference statements)
0
35
0
Order By: Relevance
“…Andrographolide induces apoptosis of colon cancer cells via the upregulation of ERS proteins GRP78, CHOP as well as the decreased BAX/Bcl-2 ration [33]. ERS pathway is also reported to participate in the malignancy of diverse cancers, such as the metastasis of breast cancer [34,35], the poor progression of gastric carcinoma [36] as well as anti-cancer drug resistance of lung cancer cells and ovarian carcinoma cells [37]. Moreover, another study also demonstrates Cellular Physiology and Biochemistry Cellular Physiology and Biochemistry that icariin exerts anti-tumor activity by upregulating the expression of ERS -related molecules (GRP78, CHOP, p-PERK and p-eIF2a), resulting in the inhibition of cell migration, adhesion and increase in apoptosis [38].…”
Section: Discussionmentioning
confidence: 99%
“…Andrographolide induces apoptosis of colon cancer cells via the upregulation of ERS proteins GRP78, CHOP as well as the decreased BAX/Bcl-2 ration [33]. ERS pathway is also reported to participate in the malignancy of diverse cancers, such as the metastasis of breast cancer [34,35], the poor progression of gastric carcinoma [36] as well as anti-cancer drug resistance of lung cancer cells and ovarian carcinoma cells [37]. Moreover, another study also demonstrates Cellular Physiology and Biochemistry Cellular Physiology and Biochemistry that icariin exerts anti-tumor activity by upregulating the expression of ERS -related molecules (GRP78, CHOP, p-PERK and p-eIF2a), resulting in the inhibition of cell migration, adhesion and increase in apoptosis [38].…”
Section: Discussionmentioning
confidence: 99%
“…GRP94 Promotes Tumorigenesis-Previous reports have indicated that GRP94 is a pro-oncogenic chaperone (13) that promotes cell adhesion and causes tumorigenesis and metastasis in various organs (56,57). A three-dimensional in vitro tumor formation assay was used to investigate whether the defects in GRP94 knockdown cells would translate into defects in tumor formation and metastasis.…”
Section: Grp94 Knockdown Cells Are Defective In the Transport Of Secrmentioning
confidence: 99%
“…On the other hand, low Fn14 expression correlated with lymph node-negative disease and well differentiated tumors, what is indicative of good prognosis [15]. Another group reported that in breast adenocarcinomas, certain proteins including Fn14 associated with the endoplasmic reticulum stress phenotype are candidate markers of brain metastases [35]. Recently, it was suggested that Fn14 protein is a valuable marker of breast carcinoma progression and might be a good prognostic marker for breast carcinoma patients [23].…”
Section: Resultsmentioning
confidence: 99%